1981
DOI: 10.1207/s15327752jpa4501_15
|View full text |Cite
|
Sign up to set email alerts
|

Further Validation of the Social Interest Index With Male Alcoholics

Abstract: The relationships between the Social Interest Index (SH) and other variables were explored in two studies of male alcoholics. The SH correlated positively with Achievement, Dominance, and Intraception of the Edwards Personal Preference Schedule and negatively with Abasement and Succorance. The SH failed to correlate positively with Affiliation and Nurturance and unexpectedly correlated negatively with Autonomy. The SH was also found to relate positively to Personal Orientation Inventory (POI) measures of inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The correlations suggested that the alcoholics with higher social interest are motivated more by the achievement of success than by the avoidance of failure and vice versa for the alcoholic with low social interest. Mozdzierz and Semyck (1981) Zarski, West, and Bubenzer (1982) examined the relationship between social interest as measured by the SII and adjustment with a sample that contained runners and nonrunners. The authors predicted that runners would report greater life adjustments as measured by the Bell Adjustment…”
Section: A Review Of the Social Interest Index Researchmentioning
confidence: 99%
“…The correlations suggested that the alcoholics with higher social interest are motivated more by the achievement of success than by the avoidance of failure and vice versa for the alcoholic with low social interest. Mozdzierz and Semyck (1981) Zarski, West, and Bubenzer (1982) examined the relationship between social interest as measured by the SII and adjustment with a sample that contained runners and nonrunners. The authors predicted that runners would report greater life adjustments as measured by the Bell Adjustment…”
Section: A Review Of the Social Interest Index Researchmentioning
confidence: 99%